Internet of Things (IoT) implementation through Node-RED to control and monitoring induction motors - Bahri, Faisal; Ta ali; Hendra, Ayu (Department of Electrical Engineering Universitas Negeri Padang, 2024)
The Internet of Things (IoT) is a technology that plays an important role in the contemporary era, especially in the industrial sector. The Internet of Things allows remote access of physical objects at any time and from any location, simply by establishing an internet connection. Thus, in the control and monitoring of motors remotely, IoT allows adjusting the speed and direction of rotor rotation. The motor used is a 0.75 kW Siemens induction motor. To adjust the speed and direction of rotor rotation of the motor, a Sinamic G120 programmable logic controller S7-1200 VSD is programmed via TIA Portal to serve as the central controller for all induction motor control. A multi-interface system consisting of a KTP 700 Comfort HMI, a PC server, and clients in the form of PC and smartphone clients was used for control and monitoring of the induction motor. The visual interface of the HMI interface was designed using TIA Portal, while the visual interface of the server and client was designed using Node-RED. The PC server, PLC, HMI, and VSD are all connected via Ethernet. At the same time, the connection of the Internet of Things (IoT) client, which is integrated with the server, is connected via the Internet network. Research on IoT-based control and monitoring of induction motors through the Node-RED proposal has been successful and works as intended